KERAGAMAN ANGGREK EPIFIT DI KAWASAN HUTAN ALAM DESA PETARIKAN, KABUPATEN KOTAWARINGIN BARAT - KALIMANTAN TENGAH - Yulia, Nina Dwi (Buletin Kebun Raya, 2008)
A study on the diversity of epiphytic orchids in the natural forest at the Village Petarikan, District Kotawaringin Barat, Central Kalimantan was carried out. All routes in the area of study were investigated. The number of epiphytic orchids found was 32 genera, consisting of 99 species. The most common species were those of genera Bulbophyllum and Dendrobium. Some of them were endemic to Kalimantan, i.e. Dendrobium nabawanense, Bulbophyllum beccarii, Dendrochilum oxylobum, Liparis lobongensis and Porpax borneensis. These orchids were frequently found on Saraca declinata, Dipterocarpus sp. and Durio zibethinus.